Strike Action and Nation Building Labor Unrest in Palestine/Israel, 1899-1951 - Vries, David De (Berghahn Books, 2015)
Strike-action has long been a notable phenomenon in Israeli society, despite forces that have weakened its recurrence, such as the Arab-Jewish conflict, the decline of organized labor, and the increasing precariousness of employment. While the impact of strikes was not always immense, they are deeply rooted in Israel's past during the Ottoman Empire and Mandate Palestine. Workers persist in using them for material improvement and to gain power in both the private and public sectors, reproducing a vibrant social practice whose codes have withstood the test of time. This book unravels the trajectory of the strikes as a rich source for the social-historical analysis of an otherwise nation-oriented and highly politicized history